Controversies over the evolutionary role of paranasal sinus pneumatization in humans and neanderthals as an adaptation to extreme cold - Dressino, Vicente (2014)
In this paper, we examine a case of scientific controversy over the evolving role of the paranasal sinuses, comparing Neanderthals and humans by analyzing two rival hypotheses. The first hypothesis states that the paranasal sinuses do not represent an adaptation to extreme cold, while the second claims the contrary. The two articles partially use the same database and employ identical methodologies and evolutionary theoretical assumptions. This example is interesting because, in terms of Nudler’s concepts of controversial and non-controversial spaces, the problem lies in the latter, i.e., the biases of the two articles and their mistakes. Our paper highlights the misunderstandings that can arise when an attempt is made to analyze a complex structure from an evolutionary perspective using two-dimensional analytical techniques, that is to say, explaining a trait in isolation and, consequently, losing an integrated approach to the organism and its multiple interactions with the environment.